![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)-3 2 +|-3|+(-1) 2013 ×(π-3) 0 -( 1 2 ) -1 (2)(x+3) 2 -...
计算:(1)-32+|-3|+(-1)2013×(π-3)0-(12)-1(2)(x+3)2-(x-1)(x-2)(3)(a+1)(a-1)(a2+1)(a4+1)(4)...
计算:(1)-3 2 +|-3|+(-1) 2013 ×(π-3) 0 -( 1 2 ) -1 (2)(x+3) 2 -(x-1)(x-2)(3)(a+1)(a-1)(a 2 +1)( a 4 +1)(4)(a-2b-3c)(a-2b+3c)
展开
1个回答
展开全部
(1)原式=-9+3-1-2=-9; (2)原式=x 2 +6x+9-(x 2 -3x+2)=x 2 +6x+9-x 2 +3x-2=9x+7; (3)原式=(a 2 -1)(a 2 +1)(a 4 +1)=(a 4 -1)(a 4 +1)=a 8 -1; (4)原式=(a-2b) 2 -9c 2 =a 2 -4ab+4b 2 -9c 2 . |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询